Comparison of the Effectiveness of Various Drug Interventions to Prevent Etomidate-Induced Myoclonus: A Bayesian Network Meta-Analysis - Zhang, Kang-Da; Wang, Lin-Yu; Zhang, Dan-Xu; Zhang, Zhi-Hua; Wang, Huan-Liang (Frontiers in Medicine, 2022)
Background: Myoclonic movement is a very common but undesirable phenomenon during induction of general anesthesia using etomidate, which may even cause some unnecessary trouble sometimes. Although more and more drugs have been shown to prevent etomidate-induced myoclonus (EM), the lack of direct comparison of the various drugs has clouded clinical decision-making. Our network meta-analysis (NMA) was used to compare the efficacy of different drugs, especially for the prevention of moderate to severe myoclonus. Methods: Based on several biomedical databases, randomized controlled trials (RCTs) published in English from inception to August, 22th 2021 were searched. Among various interventions, we mainly selected 9 types of intervention drugs (dexmedetomidine, etomidate, lidocaine, NMDA receptor antagonist, κ opioid receptor agonist, μ opioid receptor agonist, muscle relaxant, gabapentin, and midazolam) for comparison according to the number of studies. A Bayesian NMA was performed using STATA16 and R software. The relative risk of EM was assessed using risk ratios (RRs) and their corresponding 95% confidence intervals (CI). Results: 31 RCTs that involved 3209 patients were eventually included. NMA results showed that, compared with placebo, etomidate (RR 4.0, 95%CI 2.1-7.8), κ opioid receptor agonist(RR 2.9, 95%CI 1.9-4.6), μ opioid receptor agonist(RR 3.1, 95%CI 2.3-4.3), NMDA receptor antagonist(RR 1.7, 95%CI 1.0-2.8), dexmedetomidine(RR 2.4, 95%CI 1.5-3.9), lidocaine (RR 2.1, 95%CI 1.2-3.9) and midazolam (RR 2.2, 95%CI 1.5-3.2) can significantly reduce the risk of EM, While the effect of muscle relaxants(RR 2.1, 95%CI 0.81-5.3) and gabapentin (RR 2.8, 95%CI 0.92-9.3) seems to be inconclusive. Further subgroup analysis showed that preoperative low-dose etomidate (RR 0.33,95%CI 0.21-0.53), μ opioid receptor agonist (RR 0.41, 95%CI 0.32-0.53), and κ opioid receptor agonist (RR 0.48, 95%CI 0.35-0.65) were significantly better than other interventions in the prevention of moderate to severe EM. Conclusion: Preoperative use of small doses of etomidate or opioids may be the most effective way to avoid EM, especially moderate and severe EM, which makes anesthesia induction safer, more stable, and more in line with the requirements of comfort medical. PROSPERO registration number: CRD42021277063